Clinical presentation and outcome of coronavirus disease 2019 infection in chronic obstructive pulmonary disease patients - Reham M. El Morshedy; Maha M.S.A. El-Kholy; Madonna Y.R. Kelada; Abdelroauf M.S. Abdelroauf; Marwan N.E. Mohamed (Egyptian Journal of Chest Disease and Tuberculosis)
Background It was observed that coronavirus disease 2019 (COVID-19) respiratory complications might be deleterious in patients with prior chronic respiratory diseases. Chronic obstructive pulmonary disease (COPD) cases had more respiratory symptoms, elevated inflammatory markers, and a higher viral load. We aimed to identify COVID-19 presentation pattern, severity, and outcomes in COPD patients. Patients and methods This cross-sectional comparative hospital-based investigation was executed on 200 patients aged 18 years old and above, of both sexes, diagnosed with COVID-19 infection by PCR. Patients were categorized into two groups: group 1: people with COPD are included based on their prior pulmonary function test results and postbronchodilator FEV1/FVC less than 70%. Patients with COVID-19, but without COPD, are included in group 2. Results The current study included 200 patients who were subdivided into the COPD-group and the non-COPD group. There was a significant difference in smoking status, which was higher in the COPD group [69 (69%) vs. 16 (16%)] in the non-COPD group. In addition, neutrophil/lymphocytes ratio (4.04±1.07 vs. 2.35±1.13), erythrocyte sedimentation rate (56.52±14.99 vs. 46.98±25.88), C-reactive protein (41.39±6.82 vs. 21.31±14.61), ferritin (609.05±52.83 vs. 492.11±44.46), and D-dimer (5.83±1.94 vs. 1.74±0.16) levels were elevated in the COPD group compared with the non-COPD group, regarding severity grades of COVID-19. Critically ill group were more prevalent in the COPD group than the non-COPD group [67 (67%) vs. 27 (27%)]. Regarding ventilatory support, COPD patients were more in need of mechanical ventilation [34 (34%) vs. 18 (18%)] than the non-COPD group. COPD group needed to be admitted to ICUs [46 (46%) vs. 26 (26%)] than the non-COPD group. COPD group had longer length of hospital stay than the non-COPD group (13.98±2.22 vs. 8.09±1.77, respectively). Conclusion The COVID-19 cases with COPD had no difference in clinical presentation compared with the non-COPD group. Most of the COPD group had critical and severe grade of COVID-19 infection in contrast to the non-COPD group. COPD patients had higher frequency of ICU admission, more need for mechanical ventilation, longer hospital stay, and higher mortality than the non-COPD group. We found that predictors for mortality among COVID-19 patients’ infection were male sex, old age, diabetes mellitus, D-dimer, COPD disease, and severe grade of COVID-19.